2021
DOI: 10.1186/s12951-021-00788-6
|View full text |Cite
|
Sign up to set email alerts
|

pH-dependent delivery of chlorhexidine from PGA grafted mesoporous silica nanoparticles at resin-dentin interface

Abstract: Background A low pH environment is created due to the production of acids by oral biofilms that further leads to the dissolution of hydroxyapatite crystal in the tooth structure significantly altering the equilibrium. Although the overall bacterial counts may not be eradicated from the oral cavity, however, synthesis of engineered anti-bacterial materials are warranted to reduce the pathogenic impact of the oral biofilms. The purpose of this study was to synthesize and characterize chlorhexidin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(23 citation statements)
references
References 59 publications
0
23
0
Order By: Relevance
“…Until today, several studies have shown a change in the release of CHX as a result of pH change, and more articles can be found as examples for the pH-dependent properties of the PGA, but the combination of these systems can provide the base of novel treatment concepts for patients with moderate or severe periodontitis [ 6 , 42 , 45 , 46 ]. The combination of drugs to increase the effectiveness and decrease the necessary amount of the applied medicines is a long-standing endeavor.…”
Section: Resultsmentioning
confidence: 99%
“…Until today, several studies have shown a change in the release of CHX as a result of pH change, and more articles can be found as examples for the pH-dependent properties of the PGA, but the combination of these systems can provide the base of novel treatment concepts for patients with moderate or severe periodontitis [ 6 , 42 , 45 , 46 ]. The combination of drugs to increase the effectiveness and decrease the necessary amount of the applied medicines is a long-standing endeavor.…”
Section: Resultsmentioning
confidence: 99%
“…CHXloaded PLGA nanoparticles demonstrated a typical peak of Raman scattering at 638, 802, 1040, 1127, and 1446 cm À1. [25] The Raman spectrum at 1446 cm À1 for CHX-loaded/MSN-PGA is suggestive of anti-symmetric vibration from the lactic unit corresponded to CH 2 deformation which is confined to a lower intensity in CHXloaded/MSN groups. The assignments at 1040 and 1127 cm À1 correspond to CH 3 Rocking and CH 2 wagging.…”
Section: Morphological and Spectral Analysis Outcomes Of Formulated Nanoparticlesmentioning
confidence: 94%
“…After seeding of cells, 100 μl of culture medium was removed and thereafter, 20 μl of MTT reagent solution (2 mg/ml) was added to each experimental adhesive disc and incubated for 4 h at 37°C in 5% CO 2 atmosphere, followed by adding 200 μl/well of dimethyl sulfoxide (DMSO, Sigma‐Aldrich, St. Louis, MO, USA) under gentle shaking for 15 min. The absorbance was measured at 570 nm using a microplate spectrophotometer reader (Bio‐Rad, Model 680 XR, CA), and the cell viability was evaluated after 0, 24, 48, and 72 h. [ 28 ]…”
Section: Methodsmentioning
confidence: 99%